Force Drawdowns and Demographic Diversity - Lytell, Maria C.; Kuhn, Kenneth; Haddad, Abigail; Marquis, Jefferson P.; Lim, Nelson (RAND Corporation, 2023)
In January 2012, the Department of Defense (DoD) announced plans for a large-scale reduction—or drawdown—of its military force, which could have unintended consequences for demographic diversity. The Office of Diversity Management and Equal Opportunity (ODMEO) in the Office of the Under Secretary of Defense (Personnel and Readiness) asked RAND to analyze how force reductions could affect the demographic diversity of the DoD workforce.